Penerapan Konsep Green Economy Dalam Meningkatkan Pendapatan UMKM Tahu di Dusun Tahu Kabupaten Situbondo - Rizki Febri Eka Pradani; Laili Eka Amalia; Hamimah Ismawati; Ikmilul Holifah (Universitas Negeri Surabaya, 2023)
Micro Small Medium Enterprises Tofu SMEs in East Java, especially Situbondo Regency, which is located in Besuki District, Jetis Village, are SMEs that have high productivity every day. This has a close relationship with the environmental and economic impact of the surrounding community. The purpose of carrying out this research is in accordance with the formulation of the problem that has been prepared, namely to find out the application of the Green Economy and analyze the obstacles to implementing the Green Economy on the productivity of Tofu SMEs in Jetis Village, Besuki District, Situbondo Regency. The method used in this research is qualitative with triangulation data analysis technique. The results of the study show that the application of the Green Economy to Tofu SMEs has not been maximized. The implementation of the Green Economy is only focused on solid waste management. Meanwhile, the processing of liquid waste and MSME gas actors still feel difficulties due to the lack of knowledge they have. This diversification is considered very helpful for MSME actors in increasing income and opening new jobs for the surrounding community.